DAYA SAING EKSPOR MINYAK KELAPA MENTAH (CCO) INDONESIA DI NEGARA TUJUAN UTAMA - Syarafina Luthvia Sari; Arini Hardjanto (Agros Journal of Agriculture Science, 2023)
Crude coconut oil (CCO) is a coconut derivative product that has high economic value and contributes greatly to the overall export of coconut products. Indonesia is the second largest exporter of crude coconut oil in the world, but the export volume of Indonesian crude coconut oil to the main destination countries has decreased in recent years. This study aims to analyze the competitiveness of Indonesian crude coconut oil in the main destination countries and the factors that influence the export of Indonesian crude coconut oil in the main destination countries. The analytical methods used are RCA, EPD, and panel data regression. The results of RCA and EPD estimates show that Indonesia’s CCO is comparatively competitive in the Netherlands, Malaysia, and the United States and competitive in the United States, namely in the rising star position. The estimation results of the model show that the variables of Indonesia's CCO export prices have a negative effect, while the Philippines' CCO export prices and trade openness have a positive effect on the export volume of Indonesia’s CCO.